THE HR IMPACT ON ROMANIAN UNIVERSITIES EDUCATION QUALITY - Adrian Lupu (CES Working Papers, 2010)
Higher education is the main supplier of experts who will lead in the near future the Romanian society and its integrated economy into the European Union. Obtaining a quality-oriented behavior is a major constraint in the actual process of real European integration of Romania, representing meanwhile a key aspect in gathering the economic prosperity as the nation longs for more than 20 years. A major importance in this respect has the educational component. It becomes obvious that all of the universities` work must be oriented towards increasing the competitiveness of the institution both at nationally and internationally level. This can be achieved through quality work and results, a performing management, an appropriate financial policy of the rational resources` use and gathering of the new resources, strengthening the international dimension of business and encouraging a responsible attitude by the staff side. For any higher education’s institution, the quality management must become the main path to increase its performance and prestige. Unfortunately, in many universities the quality management is confused with accreditation and the efforts are being made to achieving the standards` requirement, while continuous improvement is overlooked, followed closely by an element often not taken into account in the Romanian educational process: students` perspective.